2022
DOI: 10.1002/jcla.24778
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and viral etiology of acute respiratory infection in an outpatient fever clinic during COVID‐19 pandemic in a tertiary hospital in Nanjing, China

Abstract: Background Clinical feature and viral etiology for acute respiratory infection (ARI) in the community was unknown during coronavirus disease 2019 (COVID‐19) pandemic. Objective In a retrospective study, we aimed to characterize the clinical feature and etiology for the ARI patients admitted to the outpatient fever clinic in Nanjing Drum Tower Hospital between November 2020 and March 2021. Methods Fifteen common respiratory pathogens were tested using pharyngeal swabs by multiplex reverse transcriptase‐polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Different from the infection that predominant by influenza, RVs as the most active pathogens in our study. Compared with the prevalence before COVID-19 epidemic, an increased prevalence of RVs was observed, which indicated not all pathogens were restricted by positive prevention [ 22 ]. It is suggested that the suitable strategies should be selectively used to treat specific pathogens under the background of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Different from the infection that predominant by influenza, RVs as the most active pathogens in our study. Compared with the prevalence before COVID-19 epidemic, an increased prevalence of RVs was observed, which indicated not all pathogens were restricted by positive prevention [ 22 ]. It is suggested that the suitable strategies should be selectively used to treat specific pathogens under the background of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%